Implementasi Program Kota Tanpa Kumuh (KOTAKU) Di Kelurahan Dumai Kota - Lili Suryani (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2023)
This study aims to see how the implementation of the slumless city (KOTAKU) program in Dumai Kota Village in an effort to improve people's living standards and alleviate slums in urban areas. The method used in this study is a qualitative method. The data sources in this study are primary and secondary data. The data collection techniques carried out are interviews, observations and documentation. Meanwhile, the data analysis technique carried out in this study uses the model of Miles and Huberman (2009), namely by reducing data, presenting data, and drawing conclusions. The results of this study show that the slumless city program in dumai city village has been carried out well, which is proven by the implementation of established programs such as repairing concrete roads, improving environmental drainage, repairing garbage carts and repairing fire fighting motors. This program was carried out because of the existence of policy implementers who were able to implement policies properly from the planning stage, socialization, providing training and implementing the program properly. However, in the implementation of the program, there was still a lack of participation of the local community, it can be seen that not all were attending the socialization so that there are still people who do not know about the city without slums program.